"Light cannabis" consumption in a sample of young adults: Preliminary pharmacokinetic data and psychomotor impairment evaluation. (June 2021) - Pelletti, Guido; Barone, Rossella; Giorgetti, Arianna; Garagnani, Marco; Rossi, Francesca; Fais, Paolo; Pelotti, Susi
Highlights: We investigated THC and CBD blood concentration following "light cannabis" smoking. Psychomotor and cognitive performance were assessed before and after the experiment. Only 4 subject reported blood THC concentrations higher than 2 ng/ml. No significant impairment were observed in psychomotor performance task. Our findings are indicative but not conclusive, and require replication. Abstract: Introduction: In 2019, the Italian Supreme Court established that hemp cannot be commercialized for human use, when the "psychotropic effect" of the product or its "offensiveness" can be demonstrated. The aim of the present study is to assess Δ9-tetrahydrocannabinol (Δ9-THC) and cannabidiol (CBD) blood concentrations after smoking cannabis with a low percentage of Δ9-THC, also referred as "light cannabis", and its effects on young adults' vigilance, cognitive and motor skills. Materials and methods: Eighteen young adults consumed three light cannabis cigarettes containing 400 mg of inflorescences each, with a percentage of 0.41% of Δ9-THC and of 12.41% of CBD. Blood samples were collected before the experiment (t0), after each light cannabis cigarette (t1→t3), 60 (t4) and 120 (t5) minutes after the beginning of the experiment. Five performance tasks and a subjective scale were employed for measuring cognitive and psychomotor performances the day before the experiment (TT0) and after the third cigarette (TT1). Results: Mean (SD) concentrations (ng/ml) were 1.0 (0.8) in t1, 1.2 (0.9) in t2, 1.0 (0.8) in t3, 0.6 (0.4) in t4 and 0.3 (0.3) in t5 for Δ9-THC; 10.5 (10.3) in t1, 10.3 (13.2) in t2, 15.1 (14.8) in t3, 9.9 (9.2) in t4 and 5.7 (5.7) in t5 for CBD. No significant differences were observed between TT0 and TT1 for all performed psychomotor performance task. None of the subjects declared to feel "high" after the experiment. Discussion: All study participants reported that a higher number of cigarettes, corresponding in this study to 1200 mg of herbal product, could hardly be consumed by smoking in a recreational setting. Δ9-THC and CBD concentrations showed a high inter-subject variability, and the average concentrations were lower than those previously reported. Toxicological results showed a decrease of Δ9-THC and CBD after the third light cannabis cigarette, and a Δ9-THC /CBD ratio always<1 was observed. The lack of impairment observed in our participants can be interpreted as a consequence of the very low concentrations detectable in the blood.